Intravenous immunoglobulin treatment for mild Guillain-Barré syndrome: an international observational study. Issue 10 (8th June 2021) - Verboon, Christine; Harbo, Thomas; Cornblath, David R; Hughes, Richard A C; van Doorn, Pieter A; Lunn, Michael P; Gorson, Kenneth C; Barroso, Fabio; Kuwabara, Satoshi; Galassi, Giuliana; Lehmann, Helmar C; Kusunoki, Susumu; et al.
Abstract : Objective: To compare the disease course in patients with mild Guillain-Barré syndrome (GBS) who were treated with intravenous immunoglobulin (IVIg) or supportive care only. Methods: We selected patients from the prospective observational International GBS Outcome Study (IGOS) who were able to walk independently at study entry (mild GBS), treated with one IVIg course or supportive care. The primary endpoint was the GBS disability score four weeks after study entry, assessed by multivariable ordinal regression analysis. Results: Of 188 eligible patients, 148 (79%) were treated with IVIg and 40 (21%) with supportive care. The IVIg group was more disabled at baseline. IVIg treatment was not associated with lower GBS disability scores at 4 weeks (adjusted OR (aOR) 1.62, 95% CI 0.63 to 4.13). Nearly all secondary endpoints showed no benefit from IVIg, although the time to regain full muscle strength was shorter (28 vs 56 days, p=0.03) and reported pain at 26 weeks was lower (n=26/121, 22% vs n=12/30, 40%, p=0.04) in the IVIg treated patients. In the subanalysis with persistent mild GBS in the first 2 weeks, the aOR for a lower GBS disability score at 4 weeks was 2.32 (95% CI 0.76 to 7.13). At 1 year, 40% of all patients had residual symptoms. Conclusion: In patients with mild GBS, one course of IVIg did not improve the overall disease course. The certainty of this conclusion is limited by confounding factors, selection bias and wide confidence limits. Residual symptoms were often present after one year, indicating the need for better treatments in mild GBS.